Sosialisasi Pentingnya Pendidikan Tinggi di Madrasah ‘Aliyah Raudlatul Ulum Ledokombo Jember - Husniatul Haliyah; Mita Apriliya Faradipa; Nailiyah Basirah; Izza Afkarina (Jurnal Al-Tatwir, 2022)
The socialization of the importance of higher education for MA graduates and the equivalent aims to provide understanding and motivation to MA and equialent students who will graduate so they can consider well and to the tertiary level to continue their education tp the tertiary level, considering the importance of higher education to prepare the next generation who have broad insight so that they can empowered in future national development. This activity was carried out at MARaudlatul Ulum which was attended by 3 th grade 2 class. This activity went smoothly according to plan. While the method used in this service activity is to conduct socialization and discussions related to the material of theimportance of higher education. The resultof this activity is that the participans are more understanding and motivated to continue their education to higher education after graduating from MA later